2010
DOI: 10.2172/1009764
|View full text |Cite
|
Sign up to set email alerts
|

Tc-99 Adsorption on Selected Activated Carbons - Batch Testing Results

Abstract: CH2M HILL Plateau Remediation Company (CHPRC) is currently developing a 200-West Area groundwater pump-and-treat system as the remedial action selected under the Comprehensive Environmental Response, Compensation, and Liability Act Record of Decision for Operable Unit (OU) 200-ZP-1. This report documents the results of treatability tests Pacific Northwest National Laboratory researchers conducted to quantify the ability of selected activated carbon products (or carbons) to adsorb technetium-99 (Tc-99) from 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…While the initial sensor optimizations were performed in DI water, the final tests for the sensor selectivity were conducted in a groundwater medium, the water being collected from the well 299-W19-36 at the Hanford site in Washington. The major inorganic constituents present in the groundwater are listed in Table S1 in the Supporting Information. , …”
Section: Methodsmentioning
confidence: 99%
“…While the initial sensor optimizations were performed in DI water, the final tests for the sensor selectivity were conducted in a groundwater medium, the water being collected from the well 299-W19-36 at the Hanford site in Washington. The major inorganic constituents present in the groundwater are listed in Table S1 in the Supporting Information. , …”
Section: Methodsmentioning
confidence: 99%
“…The major inorganic constituents present in the groundwater are listed in Table S2, Supporting Information. 66 The water was spiked with different concentrations of TcO 4 − ranging from 7.5 × 10 −8 to 7.5 × 10 −6 M. To visually demonstrate the response of 1·SbF 6 to TcO 4 − , a circular carbon film was divided into three segments. 1·SbF 6 was deposited on two segments (marked 1 and 3 in Figure 1), whereas 1·TcO 4 ·xH 2 O was deposited on segment 2.…”
Section: ■ Experimental Detailsmentioning
confidence: 99%
“…Water used for the batch experiments was sourced from well 299-W19-36 on the Hanford Site. The analysis (Mattigod et al 2010) is shown in Table 3.1. (b) 216 Tetrachloroethene <0.001 <0.001 Alkalinity (as CaCO 3 ) (c) 116,000 Ethyl benzene (d) 0.03 0.06 Uranium (a) 174 p/m xylene (d) Treatments to the water were completed prior to the sorption test and are summarized in Table 3.2.…”
Section: Source Watermentioning
confidence: 99%
“…The resin exchange capacities (Table 3.5), carbon loading capacity (Table 3.6), and iodine concentration of 11.0 µg/L based on previous source water analysis (Mattigod et al 2010) was used to calculate a starting solution-to-solid ratio. It was calculated that ratio #2 should remove all of the iodine in 1 L of source water.…”
Section: Batch Sorption Testsmentioning
confidence: 99%
See 1 more Smart Citation